All-Solid-State PVC Membrane Ag+-Selective Electrodes Based on Diaza-18-Crown-6 Compounds - Isildak, I; Yolcu, M; Isildak, O; Demirel, N; Topal, G; Hosgoren, H (Springer-Verlag Wien, 2004)
Two diaza-crown ether compounds were synthesized and evaluated as Ag+-selective carriers in polyvinylchloride (PVC) membrane electrodes of solid-state type. The all-solid-state PVC membrane electrode based on N,N-Dibenzyl-dibenzo-diaza-18-crown-6 exhibited a super-Nernstian response (75+/-10 mV per decade) over the concentration range of 1x10(-1) to 7x10(-6) M of Ag+ ion and a detection limit of 3x10(-6) M, at a wide range of pH (pH 4-7). The response time of the electrode was fast (less than similar to10s), and it can be used for three months without any significant deviation in potential. The proposed all-solid-state PVC membrane electrodes revealed high selectivity toward Ag+ ion with respect to alkali, alkaline earth, heavy and transition metal ions. A flow-through cell of all-solid-state PVC membrane Ag+-selective electrode based on N,N-Dibenzyl-dibenzo-diaza-18-crown-6 has also been prepared and applied for flow-injection analysis of Ag+ ion in solution.
Keywords: Diaza-Crown Ethers; All-Solid-State; PVC Membrane; Silver-Selective Electrodes; FIA